2007
DOI: 10.1007/s00125-007-0743-8
|View full text |Cite
|
Sign up to set email alerts
|

Retinol-binding protein 4 is associated with components of the metabolic syndrome, but not with insulin resistance, in men with type 2 diabetes or coronary artery disease

Abstract: Aims/hypothesis Retinol-binding protein 4 (RBP4) has recently been reported to be associated with insulin resistance and the metabolic syndrome. This study tested the hypothesis that RBP4 is a marker of insulin resistance and the metabolic syndrome in patients with type 2 diabetes or coronary artery disease (CAD) or in non-diabetic control subjects without CAD. Methods Serum RBP4 was measured in 365 men (126 with type 2 diabetes, 143 with CAD and 96 control subjects) and correlated with the homeostasis model a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
135
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(161 citation statements)
references
References 22 publications
20
135
6
Order By: Relevance
“…However, the role of RBP4 in IR seems controversial. Earlier studies (12,13) have not found any correlation between RBP4 levels and IR, which is in contrast to other reports (31,32) wherein an association of RBP4 levels and IR has been in dicated. In this study also there was no correlation between RBP4 levels and IR in any of the groups.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…However, the role of RBP4 in IR seems controversial. Earlier studies (12,13) have not found any correlation between RBP4 levels and IR, which is in contrast to other reports (31,32) wherein an association of RBP4 levels and IR has been in dicated. In this study also there was no correlation between RBP4 levels and IR in any of the groups.…”
Section: Discussioncontrasting
confidence: 79%
“…The circulatory RBP4 levels are probably linked to the proatherogenic lipids (5). Serum RBP4 levels have been significantly and independently associated with hepatic lipase activity in patients with type 2 diabetes mellitus and coronary artery disease but not with controls (12). Hepatic lipase hydrolyses VLDL TG lea ding to the accumulation of proathe rogenic small, dense LDL particles, which are accom panied by the presence of increased TG and decreased HDL in MS (36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In several studies, circulating RBP4 levels also did not correlate with insulin resistance, impaired glucose tolerance, T2D, or altered insulin secretion (10,72,(74)(75)(76)(77). In adipose tissue and muscle, insulin-sensitizing agent pioglitazone unexpectedly increased RBP4 gene expression (10).…”
Section: Rbp4 In Childhood/adolescent Obesity and Insulin Resistancementioning
confidence: 98%
“…Lowering RBP4 could be a new strategy for treating T2DM was also deduced then. However, inconsistent observations have been postulated simultaneously and continuously since the discovery of its role in IR (Erikstrup et al, 2006;Janke et al, 2006;Takashima et al, 2006;von Eynatten et al, 2007). Although there was an association between RBP4 and steatosis in G-1 CHC patients, Petta et al suggested RBP4 might be the expression of a virus-linked pathway to steatosis unrelated to IR (Petta et al, 2008).…”
Section: Retinol-binding Proteinmentioning
confidence: 99%